Enhancement of Light Absorption in the Active Layer of Organic Solar Cells using Ag:SiO2 Core-Shell Nanoparticles - Fahendri Fahendri; Ilham Perdana; Zulfi Abdullah; Mulda Muldarisnur (Jurnal Penelitian Pendidikan IPA, 2022)
Organic solar cells still suffer from relatively low conversion efficiency despite significant progress. An Ag:SiO2 core-shell nanoparticle embedded inside the active layer of an organic solar cell is expected to enhance light absorption. Light absorption within the active layer consisting of 70 nm thickness PEDOT: PSS and P3HT: PCBM was calculated using the finite element method for a variable diameter of the silver core, the thickness of the SiO2 shell, and the relative position of nanoparticle inside the active layer. The diameter of the Ag nanoparticle varies from 20 to 50 nm, the thickness of SiO2 varies from 1 to 4 nm, and the position was shifted vertically to 70 nm. The maximum light absorption in the active layer is obtained for silver nanoparticles with a diameter of 40 nm and a SiO2 thickness of 1 nm. The optimum position of the core-shell nanoparticle was found to be not at the interface between the PEDOT: PSS and P3HT: PCBM layers but a little bit shifted down into P3HT: PCBM layer. The highest increase of light absorption, compared to without Ag:SiO2, is 210%, much higher than reported in the literature. Increasing absorption is related to the excitation of surface plasmon resonance of Ag:SiO2 nanoparticles leading to the local field and scattering enhancement in the active layer of the organic solar cell